Otoacoustic emission through waves on Reissner's membrane - Reichenbach, Tobias; Stefanovic, Aleksandra; Nin, Fumiaki; Hudspeth, A. J. (AIP Conference Proceedings, 2015)
Otoacoustic emissions are a striking manifestation of mechanical activity within the cochlea. Recent experimental work has stirred a controversy concerning how these mechanical signals propagate outward to the middle ear, from which they are emitted as airborne sounds. Here we show that Reissner's membrane, an elastic structure inside the inner ear, can sustain wave propagation and can therefore transmit otoacoustic emissions from inside the cochlea to the middle ear. We first develop a theoretical description for wave propagation on the parallel basilar and Reissner's membranes. We then describe experimental measurement of the predicted Reissner's membrane wave and its role in distortion-product otoacoustic emissions.
CRIS-Team Scopus Importer:2021-02-25